Sepsis in Obstetrics: Clinical Features and Early Warning Tools. Issue 4 (July 2017) - Parfitt, Sheryl E.; Bogat, Mary L.; Hering, Sandra L.; Ottley, Charlotte; Roth, Cheryl
Abstract : Abstract: Morbidity and mortality associated with sepsis has gained widespread attention on a local, state, and national level, yet, it remains a complicated disorder that can be difficult to identify in a timely manner. Sepsis in obstetric patients further complicates the diagnosis as alterations in physiology related to pregnancy can mask sepsis indicators normally seen in the general population. If early signs of sepsis go unrecognized, septic shock can develop, leading to organ dysfunction and potential death. Maternal early warning tools have been designed to assist clinicians in recognizing early indications of illness. Through use of clinical pathway-specific tools, disease processes may be detected early, subsequently benefitting patients with aggressive treatment management and intervention. This article is the second in a series of three that discuss the importance of sepsis and septic shock in pregnancy. Risk factors, causes of sepsis, signs and symptoms, and maternal early warning tools are discussed. Abstract : Risk factors for obstetric sepsis, causes, signs and symptoms, and maternal early warning tools are discussed. A recent case is presented that highlights the potential for significant maternal morbidity when there is a delay in identification of development of sepsis during pregnancy and postpartum.